Low-cost, widespread and reproducible mold fabrication technique for PDMS-based microfluidic photonic systems - Baczyński, Szymon; Sobotka, Piotr; Marchlewicz, Kasper; Dybko, Artur; Rutkowska, Katarzyna (Photonics Letters of Poland, 2020)
In this letter the possibility of low-cost fabrication of molds for PDMS-based photonic microstructures is considered. For this purpose, three different commercially available techniques, namely UV-curing of the capillary film, 3D SLA printing and micromilling, have been analyzed. Obtained results have been compared in terms of prototyping time, quality, repeatability, and re-use of the mold for PDMS-based microstructures fabrication. Prospective use for photonic systems, especially optofluidic ones infiltrated with liquid crystalline materials, have been commented. Full Text: PDF References: K. Sangamesh, C.T. Laurencin, M. Deng, Natural and Synthetic Biomedical Polymers (Elsevier, Amsterdam 2004). [DirectLink] A. Mata et. al, "Characterization of Polydimethylsiloxane (PDMS) Properties for Biomedical Micro/Nanosystems", Biomed. Microdev. 7(4), 281 (2005). [CrossRef] I. Rodríguez-Ruiz et al., "Photonic Lab-on-a-Chip: Integration of Optical Spectroscopy in Microfluidic Systems", Anal. Chem. 88(13), 6630 (2016). [CrossRef] SYLGARD™ 184 Silicone Elastomer, Technical Data Sheet [DirectLink] N.E. Stankova et al., "Optical properties of polydimethylsiloxane (PDMS) during nanosecond laser processing", Appl. Surface Science 374, 96 (2016) [CrossRef] J.C. McDonald et al., "Fabrication of microfluidic systems in poly(dimethylsiloxane)", Electrophoresis 21(1), 27 (2000). [CrossRef] T. Fujii, "PDMS-based microfluidic devices for biomedical applications", Microelectronic Eng. 61, 907 (2002). [CrossRef] F. Schneider et al., "Process and material properties of polydimethylsiloxane (PDMS) for Optical MEMS", Sensors Actuat. A: Physical 151(2), 95 (2009). [CrossRef] T.K. Shih et al., "Fabrication of PDMS (polydimethylsiloxane) microlens and diffuser using replica molding", Microelectronic Eng. 83(11-12), 2499 (2006). [CrossRef] K. Rutkowska et al. "Electrical tuning of the LC:PDMS channels", PLP, 9, 48-50 (2017). [CrossRef] D. Kalinowska et al., "Studies on effectiveness of PTT on 3D tumor model under microfluidic conditions using aptamer-modified nanoshells", Biosensors Bioelectr. 126, 214 (2019).[CrossRef] N. Bhattacharjee et al., "The upcoming 3D-printing revolution in microfluidics", Lab on a Chip 16(10), 1720 (2016). [CrossRef] I.R.G. Ogilvie et al., "Reduction of surface roughness for optical quality microfluidic devices in PMMA and COC", J. Micromech. Microeng. 20(6), 065016 (2010). [CrossRef] D. Gomez et al., "Femtosecond laser ablation for microfluidics", Opt. Eng. 44(5), 051105 (2005). [CrossRef] Y. Hwang, R.N. Candler, "Non-planar PDMS microfluidic channels and actuators: a review", Lab on a Chip 17(23), 3948 (2017). [CrossRef]